Technology-enhanced learning influence on chemical literacy: A systematic review - Ardyansyah, Ananta; Rahayu, Sri (Eclética Química, 2024)
Chemical literacy is essential to address socio-scientific issues arising today. Technology plays a key role in increasing students’ chemical literacy. Understanding how technology improves chemical literacy can help teachers choose appropriate learning tools and strategies. A systematic review with PRISMA guidelines was conducted to map the technology widely used in current chemistry learning and know-how technology influences the development of chemical literacy based on the PISA framework. A total of 15 articles were identified as meeting the review criteria. The results show that based on the literature review, E-modules are the most commonly used technology to improve chemical literacy. Technologies such as augmented reality, Canva, e-modules, mobile apps, and websites are important for the ability to “explain phenomena scientifically”. Adobe Flash Interactive Media and Virtual Laboratories are particularly effective for “constructing and evaluating designs for scientific investigation and critical interpretation of scientific data and evidence.” Finally, search engine technology has a significant impact on the ability to “research, evaluate, and use scientific information for decision-making and action”.